Die "Acht Seligkeiten" des Prager Predigers Heinrich von St. Gallen - Šimek, Jakub (Hermaea, 2013)
Originating around 1400, this sermon cycle about the Eight Beatitudes is ascribed to Heinrich von St. Gallen. It is one of the few pieces of textual evidence surviving from the German sermon in pre-Hussite Prague. The present publication is the first critical edition of the sermon cycle. It sheds light on the cultural environment of the author and discusses the connections between the sermons and other works attributed to Heinrich von St. Gallen.